2021
DOI: 10.26655/jrweedsci.2021.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Weeds are among the main phytosanitary problems and are responsible for numerous losses in agriculture. Integrated management has become increasingly important in weed control. Therefore, the present study aimed to investigate the allelopathic effect of 24 plants on morning glory (Ipomoea purpurea L.). The tests were performed in a completely randomized design, both in in vitro and in vivo experiments. The in vitro germination data were used to calculate the time and germination index, and in the in vivo exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Experiments have shown that the aqueous extract of the leaves of Eucalyptus grandis W. Hill ex Maiden promotes the inhibition and reduction of the germination of this species' seeds (Silva et al 2015b). Castro et al (2021) also evaluated the influence of several aqueous extracts on the germination of this species, reporting early, delayed, and decreased germination.…”
mentioning
confidence: 99%
“…Experiments have shown that the aqueous extract of the leaves of Eucalyptus grandis W. Hill ex Maiden promotes the inhibition and reduction of the germination of this species' seeds (Silva et al 2015b). Castro et al (2021) also evaluated the influence of several aqueous extracts on the germination of this species, reporting early, delayed, and decreased germination.…”
mentioning
confidence: 99%